Antiproliferative activity of berberine from Coscinium fenestratum on NCI-H838 cell line - Rudeewan Tungpradit (2018)
Berberine is the main cytotoxic compound in Coscinium fenestratum. Although, cytotoxic activity of berberine on many cancer cell lines have been studied but effect of berberine on NCI-H838 cell line is still not reported. In the present study, antiproliferative activity and mechanism of berberine isolated from C. fenestratum against NCI-H838 were investigated. NCI-H838 cells were treated with various concentrations of berberine and the cytotoxic activity was evaluated by MTT method. Berberine exhibited cytotoxicity by dose and time dependent manner with the IC50 values at 24, 48 and 72 h were 111.9±7.0 μM, 92.4±1.2 μM and 68.4±7.9 μM, respectively. Additionally, apoptotic in berberine treated cell was detected by DAPI staining. The associated proteins for apoptosis were examined by western blotting and it was found that berberine downregulated Bcl-2, procaspase 3, 6, 7 and 8 but upregulated caspase 7 by dose dependent manner. Moreover, berberine induced G2/M arrest was determined by the flow cytometric method. Taken together indicated that the potential of antiperiferal activity of berberine mediated through the Bcl-2/caspase-dependent pathway and G2/M cell cycle arrest.